Bibliographic coupling and collaborative network analysis on Aerospace publications: based on scientometric approach - M, Dinakaran; P, Gomathi (Bibliotecas. Anales de investigación, 2024)
Objective. Aerospace is one of the growing industries; it has determined a particular country's economic growth. Over the preceding two decades, the aerospace sector has seen tremendous growth. Therefore, "Aerospace" has been considered for scholarly attention from the Web of Science database from 2013 to 2022. Nevertheless, in extant literature in the aerospace field, the researchers have failed to conduct a scientometric approach in collaborative network analysis and bibliographic coupling analysis. Design/Methodology/Approach. The study has been conducted using the scientometric approach to understand the current trend of aerospace publications. The software tools Bibexcel and VOS Viewer were used for analyzing the data. Further analysis was utilized through Microsoft Office and Excel statistical tools. Results/Discussion. The analyzed 20250 bibliographic data has been collected. The study's findings show that year-wise publications increased from 2013 (965) to 2022 (3,953), and the annual growth rate shows a fluctuating trend. The eminent author of the study is Wang J. He has published 146(72%) publications, and collaborative authorship shows that authors Li J and Zhang Y have highly collaborated on aerospace publications with 12(0.05%). The data from the analysis carried out are available at: https://zenodo.org/records/10663289 Conclusions. In conclusion, Peoples R China has many publications, 7421(36.54%), and Peoples R China has collaborated with the UK, the US, and Singapore. The Chinese Academy of Science institution has published 556(2.7%) of documents more than other institutions. Originality value. The findings from the study could be helpful for future research issues and directions. The present study has provided a comprehensive insight into Aerospace publication trends and collaborative networks of authors and countries and analyzed the bibliographic coupling networks between authors' countries and documents.